2013
DOI: 10.1111/btp.12021
|View full text |Cite
|
Sign up to set email alerts
|

Jaguar and Puma Activity Patterns and Predator‐Prey Interactions in Four Brazilian Biomes

Abstract: Jaguars (Panthera onca) and pumas (Puma concolor) coexist throughout the Neotropics. Using camera trapping in four Brazilian biomes, we compare the daily activity patterns of the jaguar and puma, and their relationships with their main prey species. We used a kernel density method to quantify daily activity patterns and to investigate overlap between these predators and their main prey. Both cats showed intensive nocturnal and crepuscular activity (0.69 and 0.14 kernel density, respectively, for jaguars; 0.68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
148
1
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 29 publications
14
148
1
17
Order By: Relevance
“…In fact, Porfirio et al (2016a) demonstrated that ocelots tend to tailor their activity to that of their potential prey, probably in an attempt to increase encounters. Jaguars in Amolar Mountain Ridge exhibited cathemeral behaviour, a pattern different of the observed in other areas of the Pantanal (Crawshaw & Quigley, 1991;Foster et al, 2013). Pumas were also cathemeral, which is consistent with observations of Gómez et al (2005) in Bolivia; although in Argentina, western Bolivia and Chile, pumas are crepuscular (Lucherini et al, 2009).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…In fact, Porfirio et al (2016a) demonstrated that ocelots tend to tailor their activity to that of their potential prey, probably in an attempt to increase encounters. Jaguars in Amolar Mountain Ridge exhibited cathemeral behaviour, a pattern different of the observed in other areas of the Pantanal (Crawshaw & Quigley, 1991;Foster et al, 2013). Pumas were also cathemeral, which is consistent with observations of Gómez et al (2005) in Bolivia; although in Argentina, western Bolivia and Chile, pumas are crepuscular (Lucherini et al, 2009).…”
Section: Resultssupporting
confidence: 84%
“…The remaining records were eliminated from the analysis to reduce bias (Ross et al, 2013). Then, the time of each picture was converted to solar time (Foster et al, 2013;Porfirio et al, 2016a), and observations were classified as diurnal (activity predominantly between 1 h after sunrise and 1 h before sunset), nocturnal (activity predominantly between 1 h after sunset and 1 h before sunrise) or crepuscular (period that last 1 h before to 1 h after sunrise and sunset) following Romero-Muñoz et al (2010). Based on the percentage of pictures in each category, species were classified as diurnal (< 15% of the observations were at night), nocturnal (> 85% of the observations were at night), mostly diurnal (15-35% of the observations were at night), mostly nocturnal (65-85% of the observations were at night), crepuscular (50% of the observations occurred during the crepuscular period), and the rest were classified as cathemeral (i.e.…”
Section: Nature Conservation Research заповедная наука 2018 3(2): 5mentioning
confidence: 99%
See 2 more Smart Citations
“…Los felinos de gran tamaño, como es el caso del jaguar (Panthera onca) y puma (Puma concolor) cuya distribución es simpátrica (Scognamillo et al 2003), se encuentran activos tanto de noche como de día y presentan un alto traslape en sus patrones de actividad (Sunquist y Sunquist 2002;Foster et al 2013;Hernández-Saint Martín et al 2013). Sin embargo, la diferencia parece radicar en los picos de actividad dentro de cada una de las categorías (diurno, nocturno y crepuscular) dentro del ciclo circadiano (Hernández-Saint Martín et al 2013) o en la asociación con sus presas; no obstante, estos factores no son constantes a lo largo de su distribución (Sunquist 1981;Emmons 1987;Foster et al 2010).…”
Section: Introductionunclassified